Implementasi IJEPA dalam Pengembangan Sumber Daya Manusia di Toyota Motor Manufacturing Indonesia - Sultan Syafiq; Sophiana Widiastutie (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze how the progress of economic cooperation carried out by Indonesia and Japan in the study of the development of Toyota brand car manufacturing coming from Japan. With the initial goal of only making Indonesia a market, now Toyota is giving a share to Indonesia so that it can produce cars that are sent domestically and abroad. The preliminary question of this study is what factors made Toyota then entrust all directions of its production to Indonesia? Meanwhile, the main research question of this study is what is the impact of the increase in capacity carried out by Toyota Global for the capabilities of the Indonesian industry and the economic improvements that can be felt by the Indonesian people. This research method is a qualitative analysis method using case studies, in this case economic cooperation between Indonesia and Japan in the development of capacity building at Toyota Motor Manufacturing Indonesia. The main data collection method uses a literature study technique collected from books, articles and other sources, also using a field method where the author directly examines what has been running at Toyota Motor Manufacturing Indonesia.